Molecular genetic characterization of a prenatally detected 1.484-Mb Xq13.3-q21.1 duplication encompassing ATRX and a literature review of syndromic intellectual disability and congenital abnormalities in males with a duplication at Xq13.3-q21.1 - Chih-Ping Chen; Hoi-Kin Yip; Liang-Kai Wang; Schu-Rern Chern; Shin-Wen Chen; Shih-Ting Lai; Peih-Shan Wu; Wayseen Wang (Elsevier, 2017)
Objective: We present prenatal diagnosis of dup(X)(q13.3q21.1) in a male fetus and molecular genetic analysis in three generations and a literature review of syndromic intellectual disability and congenital abnormalities in males with a duplication at Xq13.3-q21.1. Case report: A 35-year-old, primigravid woman underwent amniocentesis at 18 weeks of gestation because of advanced maternal age. The woman and her mother were phenotypically normal, and there was no intellectual disability in the maternal family. Cytogenetic analysis of cultured amniocytes revealed a karyotype of 46,XY. Simultaneous array comparative genomic hybridization (aCGH) analysis on uncultured amniotic fluid incidentally detected a 1.484-Mb microduplication of Xq13.3-q21.1 encompassing ATRX. Subsequent aCGH analysis on fetal blood, maternal blood and grandmother's blood revealed the same 1.484-Mb dup(X)(q13.3q21.1). Prenatal ultrasound findings were unremarkable with no growth restriction and no short stature. After genetic counseling of syndromic intellectual disability in males with ATRX duplication, the woman elected to terminate the pregnancy. The fetus postnatally manifested hypoplastic male external genitalia, clinodactyly, hypertelorism, midface hypoplasia, epicanthic folds and micrognathia. Conclusion: Simultaneous aCGH analysis on uncultured amniotic fluid in addition to conventional cytogenetics at amniocentesis is practical and may help in detecting unknown familial inheritance of subtle X chromosome aberrations.